Kuwentong kotse Car story - Matias, Segundo D.; Madueno, Ghani; Garcia, Edith; Bravo, Becky (Quezon City Lampara Publishing House, Inc., 2010)
"People has a story about the people who owned him. The first, Jack, never knew how to take good care of a car, that was why he was sold to Sylvia. But he got bored with Sylvia because they seldom went out. He felt better when he ended up with John Carlo;s family. John Carlo's family loved him, but when John Carlo's father met an accident, he got angry with him."
Stories with moral values.
Text in English and Filipino.
Keywords: Automobiles -- Fiction; Automobile ownership